Effect of co-application of phosphate rock with organic wastes on P fractions in a tropical loamy sand soil - Ratanavirakul, Pinyaluk; Thanachit, Suphicha; Anusontpornperm, Somchai (Agriculture and Natural Resources, 2022)
Importance of the work: Phosphate rock (PR) can be used as P fertilizer in acidic soils, but its effectiveness via direct soil application is low. Organic materials could improve its solubility and alter the soil P fractionation related to the P-supply capacity to plants. Objectives: This study was conducted under controlled laboratory conditions to determine the effect of cassava peel (CP) and cassava starch waste (CSW) on inorganic (Pi) and organic (Po) fractions in a PR-applied loamy sand. Materials & Methods: Amounts of 6.25 t/ha and 12.5 t/ha of each waste were added to separate soil samples treated with 50 kg P2O5/ha of PR, with no added PR or wastes as the control. Results: The PR contained 20.3% P2O5 with most of the P dissolved in 2% formic acid accounting for 22.25% of total P2O5 and when added to the soil, it significantly increased Pi (18.8±1.13–20.1±2.30 mg/kg) more than Po (4.92±0.58–6.61±0.71 mg/kg) contents. Phosphorus quickly transformed to more stable Pi pools after PR application (27.0–36.6% of total P), likely leading to insufficient P for the plant. Both rates of CP and CSW promoted similar PR solubility, resulting in a significant increase in all P fractions (Pi, 23.1±1.27–31.7±0.33 mg/kg; Po, 15.9.1±2.06–7.41±0.59 mg/kg). The labile Pi and Po contents were the highest at 14 and 56 d, respectively; hence, P solubilized from the more stable Po fractions could replenish labile Po. Main finding: Although most P occurred in the moderately labile fraction, the labile Pi at day 112 still showed an increasing trend, especially for the PR + CP treatment with 12.5 t/ha waste.